Proton ceramic fuel cell composite cathode, preparation method thereof and corresponding cell
By using a composite cathode with a multi-stage core-shell structure in a proton ceramic fuel cell, combined with specific material composition and preparation methods, the problem of insufficient oxygen ion conduction and oxygen reduction reaction activity of PrBaCo2O5 material is solved, and high electrochemical performance and Stability avoids cathode degradation.
Patent Information
- Application Number
- CN202411015025.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-13
AI Technical Summary
In proton ceramic fuel cells, the oxygen ion conduction characteristics of PrBaCo2O5 material are not strong, and the oxygen reduction reaction activity is insufficient. The Ba element is easy to react with CO2 in the air and Cr element in metal connectors, resulting in cathode degradation, stability and electrochemical properties. Difficult to take into account both.
Using a composite cathode with a multi-stage core-shell structure, a porous skeleton of a proton conductor material is constructed and Pr1-xCexBaCo2O5-y+δFy is formed on it as the first shell layer and lanthanum calcium iron tungsten perovskite oxide or ZnO/ SnO2 is prepared as the second shell layer, combined with a binder of ethyl cellulose and terpineol, by screen printing and solution injection method, forming a composite cathode with excellent electrochemical properties and stability.
Solve the problem of interface cracking caused by mismatch between micro-nano structure and proton conductor electrolyte, significantly reduce polarization resistance, improve electrochemical reaction activity and stability, avoid direct contact between Ba and Co elements with the atmosphere, and improve oxygen reduction reaction Catalytic activity and chemical stability.
Smart Images

Figure BDA0004965458700000061 
Figure BDA0004965458700000101 
Figure BDA0004965458700000102
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of proton ceramic fuel cells, and in particular to a proton ceramic fuel cell composite cathode with a multi-level core-shell structure, as well as a method for preparing the composite cathode and a battery prepared using the composite cathode. Background Art
[0002] Proton ceramic fuel cells (PCFCs) have the advantages of high energy conversion efficiency, environmental friendliness, and wide fuel adaptability. They have broad application prospects in distributed power stations, household cogeneration, and other fields. Their cathode materials are one of the current research hotspots. The alkaline earth metal elements occupying the A position of PrBaCo2O5 (PBC) materials provide abundant alkalinity, provide more carriers for the migration of protons, accelerate the migration of protons, and ultimately improve their electrochemical performance. However, the oxygen ion conductivity of this material is not strong, and the oxygen reduction reaction activity needs to be improved. In addition, the Ba element easily reacts with CO2 in the air and the Cr element in the metal connector to cause Ba segregation, which ultimately leads to the degradation of the cathode.
[0003] Some studies have used Ca cations to dope PBC and found that it can increase oxygen vacancies, but it reduces its electronic conductivity, and the improvement in electrochemical performance is limited, and the stability problem cannot be taken into account.
[0004] Based on the above problems, the present application proposes to construct a composite cathode with a multi-level core-shell structure. By constructing a micro-nanostructured PBC-based cathode material, the problem of interface cracking caused by the mismatch between the thermal expansion coefficient and the proton conductor electrolyte is avoided, and the electrochemical performance of the cathode is improved while taking into account stability. Summary of the invention
[0005] The purpose of the present invention is to provide a composite cathode for a proton ceramic fuel cell, and also provides a method for preparing the composite cathode and a battery prepared using the composite cathode.
[0006] Based on the above purpose, the present invention adopts the following technical solutions:
[0007] First,
[0008] A composite cathode for a proton ceramic fuel cell comprises a cathode skeleton and a first shell layer and a second shell layer sequentially loaded on the cathode skeleton; the cathode skeleton is a porous structure formed by a proton conductor material, and the first shell layer material is Pr 1- x Ce x BaCo2O 5-y+δ F y(PCBCF), x=0.05-0.15, y=0.05-0.10, δ represents the oxygen vacancy content; the second shell layer is one of lanthanum calcium iron tungsten perovskite oxide (LCFW), ZnO, SnO2 or a SnO2@ZnO composite layer.
[0009] Furthermore, the element composition of the proton conductor material forming the cathode skeleton is BaZr n Ce 0.8- n Y 0.1 Yb 0.1 O3(BZCYYb), wherein 0<n≤0.8; as a more preferred solution, n=0.1, that is, the element composition of the proton conductor material forming the cathode skeleton is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3.
[0010] The first shell material is Pr 0.95 Ce 0.05 BaCo2O 4.95+δ F 0.05 .
[0011] The element composition of the lanthanum calcium iron tungsten perovskite oxide is La 0.65 Ca 0.35 Fe 0.9 W 0.1 O3.
[0012] Second,
[0013] The method for preparing the composite cathode of the proton ceramic fuel cell described in the first aspect comprises the following steps:
[0014] S1. Mixing the proton conductor material powder with the necessary binder to prepare a slurry; applying the slurry to the electrolyte surface by screen printing, and forming a cathode skeleton after calcination;
[0015] S2, taking metal nitrate and barium fluoride according to the stoichiometric ratio of the first shell material, dissolving them in a mixed solution of distilled water and ethylene glycol to prepare a precursor solution of the first shell;
[0016] S3, injecting the precursor solution of the first shell layer into the surface of the cathode skeleton, and obtaining a single-stage core-shell structure cathode after calcination;
[0017] S4. Forming a lanthanum perovskite oxide coating layer on the first shell layer by a solution injection method, or performing atomic layer deposition of Zn or Sn oxide on the surface of the first shell layer to form a second shell layer.
[0018] The binder is made of ethyl cellulose, pineol and fish oil.
[0019] The preparation method of the binder is as follows: dissolving ethyl cellulose in pine alcohol to prepare a 4wt% ethyl cellulose pine alcohol solution, heating the solution in an oil bath to 80±5°C and stirring for 10h, cooling the solution to room temperature after stirring, and setting the solution aside.
[0020] The weight ratio of the proton conductor material powder to the binder is (4-6):(6-4).
[0021] Furthermore, most slurries also include carbon powder, that is, the proton conductor material powder (BZCYYb powder) is mixed with a binder and carbon powder in a weight ratio of (4-6):(6-4):1 and fully ground to prepare a slurry.
[0022] Furthermore, the preparation method of the first shell layer precursor solution is: Pr, Ce, Ba, Co nitrates and BaF2 are dissolved in a mixed solution of distilled water and ethylene glycol according to the stoichiometric ratio (the volume ratio of distilled water to ethylene glycol is 3:1), citric acid and EDTA are used as complexing agents, and ammonia water is added to adjust the pH to 7.0±0.5 to prepare a solution with a metal ion concentration of 0.05 mol / L.
[0023] In step S1, the calcination temperature is 1000-1200° C., and the calcination time is 2-3 hours.
[0024] In step S3, the calcination temperature is 1050-1100° C., and the calcination time is 2-3 hours.
[0025] In step S4, the solution injection method is specifically: prepare a precursor solution according to the stoichiometric ratio of lanthanum calcium iron tungsten perovskite oxide, and then inject the precursor solution into the surface of the first shell layer, calcining (calcination temperature is 1050-1100 ° C, calcination time is 2-3h), and forming a second shell layer. Among them, the preparation method of the precursor solution is: take La, Ca, Fe nitrate and WO3 according to the stoichiometric ratio and add them to a mixed solution of deionized water and isopropanol (the volume ratio of deionized water to isopropanol is 1:4) to prepare a solution with a metal ion concentration of 0.05 mol / L; add glycine as a chelating agent to control the formation of the phase, the molar ratio of glycine to metal ions is 1.5:1, and stir until completely dissolved; add polyvinyl pyrrolidone (PVP) as a surfactant to improve the wettability of the solution on the skeleton, the amount added is 5% of the weight of LCFW, and stir until completely dissolved.
[0026] As another solution, in step S4, the surface deposition uses diethyl zinc or tin tetrachloride as a precursor to form a ZnO or SnO2 deposition layer on the surface of the first shell layer by atomic layer deposition.
[0027] The deposition amount of the second shell layer is 50 to 150 cycles.
[0028] Furthermore, the proton conductor material forming the cathode skeleton is prepared by the following method: nitrates of Ba (barium), Zr (zirconium), Ce (cerium), Y (yttrium) and Yb (ytterbium) are dissolved in deionized water according to a stoichiometric ratio, EDTA and citric acid are added, ammonia water is added to adjust the pH value to 7.0±0.5, and the mixture is stirred and heated until a gel precursor is formed; the gel precursor is dried, ground and calcined to obtain a proton conductor material powder BZCYYb.
[0029] In the process of preparing BZCYYb powder, EDTA and citric acid are added according to the molar ratio of the total metal cations: EDTA: citric acid = 1.0:1.0:(1.5-3.0); the mixture is heated to 80-90° C. in an oil bath while stirring, and stirring is continued until a gel precursor is formed; the gel precursor is dried, ground, and then calcined at 1000-1100° C. for 2-3 hours.
[0030] The electrolyte is a proton conductor having the same elemental composition as the proton conductor material forming the cathode skeleton.
[0031] A proton ceramic fuel cell comprises the proton ceramic fuel cell composite cathode described in the first aspect.
[0032] The present application uses a proton conductor material to construct a cathode skeleton with a porous structure, then injects a first shell precursor solution into the cathode skeleton, and forms a first shell after calcination; then wraps LCFW on the surface of the first shell, or deposits Zn and / or Sn oxides to form a composite cathode with a multi-level core-shell structure. By constructing a composite cathode with a multi-level core-shell structure, the present application achieves the following technical effects:
[0033] 1) The problem of mismatch between the thermal expansion coefficient of the micro-nanostructured PBC cathode film and the electrolyte has been solved;
[0034] 2) The polarization resistance of the constructed multi-level core-shell composite cathode is significantly reduced, and the electrochemical reaction activity is improved;
[0035] 3) The cathode polarization resistance increment of the multi-stage core-shell composite cathode after Cr poisoning treatment is smaller, showing better stability;
[0036] 4) It avoids direct contact between Ba and Co elements and the atmosphere, reducing the possibility of resistance phase generation;
[0037] 5) The composite cathode provided by the present invention is used to prepare a battery, which has excellent catalytic activity for oxygen reduction reaction and good chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is the X-ray diffraction pattern of different cathode powders prepared in Example 1;
[0039] Figure 2 This is the SEM image of the BZCYYb skeleton and LCFW@PCBCF@BZCYYb cathode. Figure 2 (a) is the SEM image of the BZCYYb skeleton. Figure 2 (b) is the SEM image of the LCFW@PCBCF@BZCYYb cathode;
[0040] Figure 3 is the electrochemical impedance spectra of the LCFW@PCBCF@BZCYYb symmetric battery and the reference battery, where Figure 3 (a) to Figure 3 (d) The corresponding LCFW:PCBCF molar ratios are (a) 7:3, (b) 6:4, (c) 5:5, and (d) 4:6. Figure 3 (e) corresponds to PCBCF@BZCYYb, Figure 3 (f) corresponds to LCFW@BZCYYb;
[0041] Figure 4 This is the polarization impedance change diagram of the LCFW@PCBCF@BZCYYb symmetrical battery after 200 hours of operation;
[0042] Figure 5 (a) and Figure 5 (b) The impedance spectra of PCBCF@BZCYYb cathode and LCFW@PCBCF@BZCYYb cathode before and after direct contact with the metal interconnect at 700℃ for 50h;
[0043] Figure 6 The Raman spectra of LCFW@PCBCF and PCBCF symmetric cells before and after direct contact with metal interconnects at 700°C for 50 h;
[0044] Figure 7 This is the full XPS spectrum obtained in Example 2;
[0045] Figure 8 This is the polarization impedance spectrum of the ZnO@PCBCF@BZCYYb symmetric battery at 550-700℃ corresponding to different ZnO deposition amounts. Figure 8 a corresponds to 0 cycle (no ZnO deposition), Figure 8 b corresponds to 50 cycles, Figure 8 c corresponds to 100 cycles, Figure 8 d corresponds to 150 cycles;
[0046] Fig. 9This is the polarization impedance spectrum of the SnO2@PCBCF@BZCYYb symmetric battery at 550-700℃ corresponding to different SnO2 deposition amounts. Fig. 9 a corresponds to 0 cycles (no SnO2 deposition), Fig. 9 b corresponds to 50 cycles, Fig. 9 c corresponds to 100 cycles, Fig. 9 d corresponds to 150 cycles;
[0047] Fig.10 It is the polarization impedance spectrum of the test cell corresponding to sample 1-1 before and after direct contact with the metal interconnector at 700°C for 50 hours;
[0048] Fig.11 It is the polarization impedance spectrum of the test cell corresponding to sample 2-1 before and after direct contact with the metal interconnector at 700°C for 50 hours;
[0049] Fig.12 This is the full XPS spectrum of SnO2@ZnO@PCBCF powder;
[0050] Fig.13 is the electrochemical impedance spectrum of the symmetrical battery with different ZnO and SnO2 deposition ratios, where Fig.13 (a) The corresponding ZnO and SnO2 deposition ratio is 4:6, Fig.13 (b) is 5:5, Fig.13 (c) 6:4;
[0051] Fig.14 (a) and 14(b) correspond to the EIS spectra of SnO2@ZnO@PCBCF and PCBCF cathode and metal interconnect before and after direct contact at 700℃ for 50h. DETAILED DESCRIPTION
[0052] The present invention is further described below in conjunction with specific examples. If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0053] Example 1
[0054] 1.1 Preparation of LCFW@PCBCF@BZCYYb core-shell structure composite cathode
[0055] A composite cathode of a proton ceramic fuel cell comprises a cathode skeleton and a first shell layer and a second shell layer sequentially loaded on the cathode skeleton; wherein the cathode skeleton is a porous structure formed by a proton conductor material, and the element composition of the proton conductor material in this embodiment is BaZr 0.1 Ce 0.7 Y 0.1 Yb0.1 O3, the first shell material is Pr 0.95 Ce 0.05 BaCo2O 4.95+δ F 0.05 , δ represents the oxygen vacancy content; the second shell is LCFW.
[0056] The preparation method of the composite cathode comprises the following steps:
[0057] S1. Preparation of cathode skeleton
[0058] S101. Prepare a proton conductor material that forms a cathode skeleton: dissolve nitrates of Ba (barium), Zr (zirconium), Ce (cerium), Y (yttrium) and Yb (ytterbium) in deionized water according to a stoichiometric ratio, add EDTA and citric acid in a molar ratio of the total of metal cations: EDTA: citric acid = 1.0:1.0:1.5, and add aqueous ammonia to adjust the pH value to 7.0±0.5; heat to 80±5°C in an oil bath while stirring, and continue stirring until a gel-like precursor is formed; dry and grind the obtained gel-like precursor, and then calcine at 1000°C for 2h to obtain BZCYYb powder, which is the proton conductor material that forms a cathode skeleton.
[0059] S102, preparing a binder: dissolving ethyl cellulose in pineol to prepare a 4 wt % ethyl cellulose-pineol solution, heating the solution in an oil bath to 80±5° C. and stirring for 10 h, cooling the solution to room temperature after stirring, and setting it aside.
[0060] S103. Preparation of cathode skeleton: Mix proton conductor material powder (BZCYYb powder) with binder and carbon powder in a weight ratio of 4:6:1 and grind them thoroughly to prepare slurry; transfer the slurry to the surface of the electrolyte (the electrolyte is a proton conductor and has the same elemental composition as the proton conductor material forming the cathode skeleton) by screen printing, and calcine at 1000°C for 3h to form a cathode skeleton.
[0061] S2, according to the first shell material Pr 0.95 Ce 0.05 BaCo2O 4.95+δ F 0.05The stoichiometric ratio of Pr (praseodymium), Ce (cerium), Ba (barium), Co (cobalt) nitrate and BaF2 are dissolved in a mixed solution of distilled water and ethylene glycol (the volume ratio of distilled water to ethylene glycol is 3:1), citric acid and EDTA are used as complexing agents, and ammonia water is added to adjust the pH to 7.0 ± 0.5 to prepare a solution with a metal ion concentration of 0.05 mol / L as a precursor solution for the first shell layer. The inventor tried different concentrations when preparing a mixed solution of metal nitrate and barium fluoride, and found that when the concentration was 0.05 mol / L, the metal ions in the first shell layer precursor solution could be better attached to the surface of the cathode skeleton and form a shell layer.
[0062] S3. Inject the precursor solution of the first shell layer into the surface of the cathode skeleton, calcine at 1050° C. for 3 h, and obtain a single-stage core-shell structure cathode.
[0063] S4. According to the stoichiometric ratio, La (lanthanum), Ca (calcium), Fe (iron) nitrate and WO3 are added to a mixed solution of deionized water and isopropanol (the volume ratio of deionized water to isopropanol is 1:4) to prepare a solution with a metal ion concentration of 0.05 mol / L; glycine is added as a chelating agent to control the formation of the phase, and the molar ratio of glycine to metal ions is 1.5:1, and stirred until completely dissolved; polyvinyl pyrrolidone (PVP) is added as a surfactant to improve the wettability of the solution on the skeleton, and the amount added is 5% of the weight of LCFW, and stirred until completely dissolved to obtain a second shell layer precursor solution; the second shell layer precursor solution is injected onto the surface of the first shell layer, and calcined at 1050°C for 3h to form a second shell layer.
[0064] 1.2 Phase structure analysis
[0065] In order to detect the phase structure and chemical compatibility of the cathode and the skeleton, LCFW, PCBCF and BZCYYb powders were prepared with reference to Example 1.1. At the same time, BZCYYb was mixed with LCFW and PCBCF powders in a weight ratio of 1:1:1 and kept at 1050°C for 3 h to simulate the preparation of LCFW@PCBCF@BZCYYb composite cathode samples in Example 1.1.
[0066] XRD analysis was performed on LCFW, PCBCF, BZCYYb powders, and LCFW@PCBCF@BZCYYb. Figure 1 As shown. Figure 1 It can be seen that LCFW and PCBCF in LCFW@PCBCF@BZCYYb are well phased, and no secondary phase is generated among the three, indicating that they have good chemical compatibility during solution injection and subsequent heat treatment.
[0067] Figure 2is the SEM image of BZCYYb skeleton and LCFW@PCBCF@BZCYYb cathode, where Figure 2 (a) is the SEM image of the BZCYYb skeleton. Figure 2 (b) is the SEM image of LCFW@PCBCF@BZCYYb cathode. Figure 2 (a) shows that the BZCYYb cathode skeleton is well connected, the grain surface is smooth, and it has a large number of pores, allowing O2 transport; the first shell and second shell formed by injection form a dense coating of smaller particles on the skeleton, providing more adsorption sites for the cathode reaction.
[0068] 1.3 Electrochemical performance analysis
[0069] In order to evaluate the effect of the injection ratio of LCFW and PCBCF on the electrochemical performance of the core-shell cathode battery, composite cathode samples with different injection amounts were prepared with reference to Example 1.1, wherein the molar ratios of LCFW and PCBCF were 7:3, 6:4, 5:5, and 4:6, respectively.
[0070] A double cathode symmetric battery with a structure of cathode|electrolyte|cathode was further prepared. Specifically, the battery structure in this embodiment was expressed as: LCFW@PCBCF@BZCYYb|BZCYYb|LCFW@PBCF@BZCYYb.
[0071] Using the four-electrode method, a perturbation voltage of 0.01 V was applied to the battery under open circuit voltage (OCV) conditions to test the impedance of the symmetrical battery. The test frequency range was set to 10 6 -10 -1 Hz, the test temperature range is 550-700℃, the temperature interval is 50℃, and the electrochemical impedance spectroscopy (EIS) in the air atmosphere is tested. Figure 3 Table 1 lists
[0072] Polarization impedance values of LCFW@PCBCF@BZCYYb, LCFW@BZCYYb, and PCBCF@BZCYYb symmetrical batteries at 550-700℃.
[0073] Table 1 R of symmetrical cells with different cathodes at 550-700℃ p
[0074]
[0075] Figure 3 The results in Table 1 show that at 700°C, when LCFW:PCBCF=7:3, 6:4, 5:5, and 4:6, the battery polarization resistance (ASR) is 0.1499, 0.1329, 0.0527, and 0.1217 Ωcm, respectively.2 . That is to say, when LCFW:PCBCF=5:5=1:1, the cathode exhibits the best electrochemical performance. We compared this result with the electrochemical performance of LCFW and PCBCF single cathodes, and the results showed that the polarization resistance values of LCFW@PCBCF@BZCYYb, LCFW@BZCYYb, and PCBCF@BZCYYb cathode symmetric cells at 700℃ were 0.0527, 0.1087, and 0.0847Ωcm, respectively. 2 The polarization impedance value of LCFW@PCBCF@BZCYYb symmetrical battery decreased by 52% and 38% compared with LCFW@BZCYYb and PCBCF@BZCYYb batteries, respectively.
[0076] 1.4 Stability Analysis
[0077] In order to explore the stability of the cathode, the polarization impedance of the LCFW@PCBCF@BZCYYb symmetric battery was tested at 550°C. Figure 4 As shown in Figure 2, after the battery has been running for 200 hours, the polarization impedance is still maintained at 1.2Ωcm 2 This indicates that the core-shell structure cathode has excellent stability.
[0078] In order to explore the poisoning phenomenon of Cr in the metal interconnect on PCBCF@BZCYYb and LCFW@PCBCF@BZCYYb, the SUS430 interconnect was directly contacted with the cathode at 700℃ for 50h, and the performance changes of the symmetrical batteries of PCBCF@BZCYYb and LCFW@PCBCF@BZCYYb were observed. The results are shown in Figure 5 It can be seen that the polarization impedance of PCBCF@BZCYYb cathode at 700℃ is reduced from 0.0880Ωcm to 2 Increased to 0.1135Ωcm 2 , the growth rate is 29.0%. Under the same conditions, the polarization impedance of LCFW@PCBCF@BZCYYb cathode is 0.0687Ωcm 2 Increased to 0.0780Ωcm 2 , with a growth rate of 13.5%. It can be seen that the core-shell structure improves the resistance of PCBCF to Cr poisoning and has excellent ORR stability.
[0079] The excellent anti-chromium performance of LCFW@PCBCF can be further confirmed by Raman analysis on the surface. Figure 6 As shown in Figure 2, the PCBCF symmetric cell was directly contacted with the metal interconnector for 50 hours, and it was found that the treated PCBCF showed obvious Raman spectral peaks of Cr-related substances, about 400 cm -1The peak is the characteristic peak of Cr2O3, 857cm -1 The peak is the characteristic peak of BaCrO4. In comparison, the characteristic peaks of Cr2O3 and BaCrO4 were almost undetectable in the LCFW@PCBCF cathode, which indicates that the cathode's resistance to chromium poisoning is enhanced after long-term Cr treatment, which is consistent with the lower growth rate of the symmetrical cell polarization impedance of the LCFW@PCBCF cathode.
[0080] Example 2
[0081] 2.1 Preparation of composite cathodes with different ZnO deposition amounts
[0082] A composite cathode of a proton ceramic fuel cell comprises a cathode skeleton and a first shell layer and a second shell layer sequentially loaded on the cathode skeleton; wherein the cathode skeleton is a porous structure formed by a proton conductor material, and the element composition of the proton conductor material in this embodiment is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3, the first shell material is Pr 0.95 Ce 0.05 BaCo2O 4.95+δ F 0.05 , δ represents the oxygen vacancy content; the second shell is ZnO.
[0083] The preparation method of the composite cathode comprises the following steps:
[0084] S1. Prepare a cathode skeleton according to Example 1;
[0085] S2. Prepare the first shell layer precursor solution according to Example 1;
[0086] S3. Inject the precursor solution of the first shell layer into the surface of the cathode skeleton, calcine at 1100° C. for 2 h, and obtain a single-stage core-shell structure cathode.
[0087] S4, using diethyl zinc as a precursor, depositing ZnO on the surface of the first shell layer by atomic layer deposition to obtain a second shell layer, and forming a composite cathode with a multi-level core-shell structure after the deposition is completed. During deposition, three different deposition amounts are set to prepare different samples, namely 50 cycles, 100 cycles, and 150 cycles, and the obtained composite cathodes are marked as sample 1-1 (50 cycles), sample 1-2 (100 cycles), and sample 1-3 (150 cycles). At the same time, refer to steps S1-S3 to prepare a comparative sample 1 (0 cycle) without depositing the second shell layer.
[0088] 2.2 Preparation of composite cathodes with different SnO2 deposition amounts
[0089] A composite cathode of a proton ceramic fuel cell comprises a cathode skeleton and a first shell layer and a second shell layer sequentially loaded on the cathode skeleton; wherein the cathode skeleton is a porous structure formed by a proton conductor material, and the element composition of the proton conductor material in this embodiment is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3, the first shell material is Pr 0.95 Ce 0.05 BaCo2O 4.95+δ F 0.05 , δ represents the oxygen vacancy content; the second shell is SnO2.
[0090] The preparation method of the composite cathode comprises the following steps:
[0091] S1. Prepare a cathode skeleton according to Example 1;
[0092] S2. Prepare the first shell layer precursor solution according to Example 1;
[0093] S3. Inject the precursor solution of the first shell layer into the surface of the cathode skeleton, calcine at 1100° C. for 2 h, and obtain a single-stage core-shell structure cathode.
[0094] S4. Using tin tetrachloride as a precursor, SnO2 is deposited on the surface of the first shell layer by atomic layer deposition to obtain a second shell layer. After the deposition is completed, a composite cathode with a multi-level core-shell structure is formed. During deposition, three different deposition amounts are set to prepare different samples, namely 50 cycles, 100 cycles, and 150 cycles. The obtained composite cathodes are marked as sample 2-1 (50 cycles), sample 2-2 (100 cycles), and sample 2-3 (150 cycles). At the same time, refer to steps S1-S3 to prepare a comparative sample 2 (0 cycle) without depositing the second shell layer.
[0095] 2.3 Phase analysis
[0096] X-ray photoelectron spectroscopy (XPS) was performed on sample 1-1 (ZnO@PCBCF) and sample 2-1 (SnO2@PCBCF), and the obtained XPS full spectrum is shown in the figure below. Figure 7 First, the elements such as Pr, Ce, Ba, Co, and F can confirm the formation of PCBCF; secondly, the presence of characteristic peaks of Zn 2p and Sn 4s orbits indicates that ZnO and SnO2 are successfully deposited on the cathode surface of PCBCF.
[0097] 2.4 Electrochemical performance analysis
[0098] A proton ceramic fuel cell is a solid oxide fuel cell with a symmetrical dual cathode structure, represented by cathode|electrolyte|cathode, wherein the electrolyte has the same cathode skeleton, and the cathode is a composite cathode prepared by Example 2.1 or 2.2.
[0099] In order to evaluate the electrocatalytic activity of the deposited PCBCF cathode, a perturbation voltage of 0.01 V was applied to the battery under open circuit voltage (OCV) conditions using the four-electrode method to test the impedance of the symmetrical battery. The test frequency range was set to 10 6 ~10 -1 Hz, the test is carried out in air atmosphere, the test temperature range is 550~700℃, and the temperature interval is 50℃.
[0100] Figure 8 is the polarization impedance spectrum of the ZnO@PCBCF@BZCYYb symmetric battery at 550-700°C corresponding to the comparative sample 1 (0 cycle) and sample 1-1 (50 cycles), sample 1-2 (100 cycles), and sample 1-3 (150 cycles) in Example 1, wherein Figure 8 a corresponds to 0 cycle (no ZnO deposition), Figure 8 b corresponds to 50 cycles, Figure 8 c corresponds to 100 cycles, Figure 8 d corresponds to 150 cycles. Figure 8 It can be seen that at 700°C, the polarization impedance values of the symmetrical battery at 0, 50, 100, and 150 cycles are 0.0820, 0.0697, 0.0782, and 0.0799 Ωcm, respectively. 2 The cathode performance of PCBCF deposited for 50 cycles is the best. At 700°C, the polarization resistance of the battery deposited for 50 cycles is reduced by about 15% compared with the battery without deposition. This shows that ZnO deposition effectively improves the catalytic activity of PCBCF cathode.
[0101] Fig. 9 It is the polarization impedance spectrum of the SnO2@PCBCF@BZCYYb symmetric battery at 550-700°C corresponding to the comparative sample 2 (0 cycle) and sample 2-1 (50 cycles), sample 2-2 (100 cycles), and sample 2-3 (150 cycles) in this embodiment 2.2, wherein Fig. 9 a corresponds to 0 cycles (no SnO2 deposition), Fig. 9 b corresponds to 50 cycles, Fig. 9 c corresponds to 100 cycles, Fig. 9 d corresponds to 150 cycles. Fig. 9 It can be seen that at 700°C, the polarization impedance values of the symmetrical battery at 0, 50, 100, and 150 cycles are 0.0820, 0.0605, 0.0975, and 0.1350 Ωcm, respectively. 2This shows that the symmetrical battery with 50 cycles of deposition has the best performance. At 700°C, the polarization resistance of the symmetrical battery with 50 cycles of deposition is reduced by about 26% compared with the battery without deposition. This shows that SnO2 has a significant effect on improving the electrochemical performance of the battery.
[0102] 2.5 Stability Analysis
[0103] In order to explore the effect of ZnO and SnO2 deposition on the anti-chromium poisoning performance of PCBCF cathode, the symmetrical cells corresponding to the 50-cycle deposited ZnO@PCBCF@BZCYYb (sample 1-1) and SnO2@PCBCF@BZCYYb (sample 2-1) selected in Example 2.4 were directly contacted with the metal connector and kept at 700°C for 50h. The polarization resistance of the cells before and after contact was measured. The experimental results are shown in Figure 2. Fig.10 and Fig.11 It can be seen that the polarization resistance of the ZnO@PCBCF@BZCYYb and SnO2@PCBCF@BZCYYb symmetric cells increased by 15% and 24% respectively after contacting the metal interconnect, while the growth rate of PCBCF@BZCYYb was 29%, indicating that the deposition of ZnO and SnO2 makes the PCBCF cathode more resistant to Cr poisoning, indicating that the multi-level core-shell structure cathode has higher chemical stability.
[0104] Example 3
[0105] 3.1 Preparation of SnO2@ZnO@PCBCF@BZCYYb core-shell structure composite cathode
[0106] The steps of preparing a composite cathode having a second shell layer as a SnO2@ZnO composite layer include:
[0107] S1. Prepare a cathode skeleton according to Example 1;
[0108] S2. Prepare the first shell layer precursor solution according to Example 1;
[0109] S3, injecting the precursor solution of the first shell layer into the surface of the cathode skeleton, calcining at 1100° C. for 2 h, and obtaining a single-stage core-shell structure cathode;
[0110] S4. Referring to Example 2, ZnO is first deposited, and after the required number of cycles are completed, SnO2 is deposited in the second step.
[0111] 3.1 Analysis of surface element valence
[0112] XPS analysis has high surface sensitivity and can better measure surface components. Fig.12The full XPS spectrum of the PCBCF powder surface after ZnO and SnO2 deposition is shown. First, the characteristic peaks of Pr, Ce, Ba, Co, and F are all displayed, and then the characteristic peaks of Zn 2p and Sn 4s are found at ~1020eV and ~140eV, indicating that ZnO and SnO2 are successfully prepared.
[0113] 3.2 Electrochemical performance analysis
[0114] Through Example 2, we know that the electrochemical performance of the symmetrical battery is best when the deposition number is 50 cycles. Therefore, on this basis, we explored the deposition ratio of ZnO and SnO2 when the total deposition number remains unchanged. The deposition times of ZnO and SnO2 are 20 and 30 times, 25 and 25 times, 30 and 20 times, that is, the ratios are 4:6, 5:5, and 6:4, respectively. The electrochemical impedance test results are as follows: Fig.13 As shown in the figure, by comparison, when the deposition ratio of ZnO and SnO2 is 5:5 or 1:1, the polarization impedance of the symmetrical battery is the smallest, which is 0.0510Ωcm at 700℃. 2 Compared with single deposition, it shows better electrochemical performance, and compared with PCBCF cathode, the polarization impedance of the symmetrical cell of composite deposition decreases by about 38%. Table 2 shows the polarization impedance of cathodes with different deposition ratios at 550-700℃.
[0115] Table 2 R of SnO2@ZnO@PCBCF cathode symmetric cells with different deposition ratios at 550-700℃ P
[0116]
[0117] 3.3 Stability analysis
[0118] The high-temperature oxidation-resistant alloys used for interconnection in SOFC usually contain chromium as an alloying element. Without an effective protective coating, the gaseous chromium produced will cause the performance of the SOFC cathode in the oxygen reduction reaction to deteriorate rapidly. To address this problem, we used atomic layer deposition technology to nano-modify the cathode surface. Fig.14 (a) is the polarization impedance spectrum of the SnO2@ZnO@PCBCF cathode (ZnO and SnO2 deposition ratio) before and after direct contact with the metal connector at 700℃ for 50 hours. It can be seen that the polarization impedance values before and after contact are 0.0555 and 0.0683Ωcm, respectively. 2 For comparison, we used PCBCF cathode to do the same treatment, and the results are as follows Fig.14 As shown in (b), the cathode polarization impedance values of PCBCF before and after treatment are 0.0884 and 0.1143Ωcm respectively. 2 .
[0119] Table 3 R0 and RP values of SnO2@ZnO@PCBCF cathode symmetric cells before and after contact with metal interconnects at 700℃ for 50h
[0120]
[0121] By comparison, the cathodic polarization impedance of SnO2@ZnO@PCBCF and PCBCF increased by 0.0128 and 0.0259 Ω cm, respectively. 2 , indicating that the cathode after deposition exhibits better resistance to Cr poisoning. In addition, we also recorded the R0 and R P The values are shown in Table 3. The mechanism of the stable ORR activity of the nanostructured PCBCF cathode may come from the geometric confinement of the nanoparticles by the coating layer, resulting in anti-agglomeration and retention of the original high specific surface area. Otherwise, the unconstrained and freely grown PCBCF nanoparticles would rapidly lose surface area and catalytic activity at high temperatures. The large retention of ASR by the nanoscale SnO2@ZnO coating layer indicates that the deposited layer plays a crucial role in preventing element enrichment from occurring.
Claims
1. A composite cathode for a proton ceramic fuel cell, comprising a cathode skeleton and a first shell layer and a second shell layer sequentially supported on the cathode skeleton; the cathode skeleton is a porous structure formed by a proton conductor material, and the first shell layer material is Pr 1- x Ce x BaCo2O 5-y+δ F y , x=0.05-0.15, y=0.05-0.10, δ represents the oxygen vacancy content; the second shell layer is one of lanthanum calcium iron tungsten perovskite oxide, ZnO, SnO2 or a SnO2@ZnO composite layer.
2. The composite cathode of a proton ceramic fuel cell according to claim 1, characterized in that: The element composition of the proton conductor material forming the cathode skeleton is BaZr n Ce 0.8-n Y 0.1 Yb 0.1 O3, where 0<n≤0.
8.
3. The composite cathode of a proton ceramic fuel cell according to claim 1, characterized in that: The first shell material is Pr 0.95 Ce 0.05 BaCo2O 4.95+δ F 0.05 .
4. The proton ceramic fuel cell composite cathode according to claim 1, characterized in that: The element composition of the lanthanum calcium iron tungsten perovskite oxide is La 0.65 Ca 0.35 Fe 0.9 W 0.1 O3.
5. The method for preparing a composite cathode of a proton ceramic fuel cell according to any one of claims 1 to 4, characterized in that the steps include: S1. Mixing the proton conductor material powder with necessary binder to prepare slurry; The slurry is applied to the electrolyte surface by screen printing, and is calcined to form a cathode skeleton; S2, taking metal nitrate and barium fluoride according to the stoichiometric ratio of the first shell material, dissolving them in a mixed solution of distilled water and ethylene glycol to prepare a precursor solution of the first shell; S3, injecting the precursor solution of the first shell layer into the surface of the cathode skeleton, and obtaining a single-stage core-shell structure cathode after calcination; S4. Forming a lanthanum perovskite oxide coating layer on the first shell layer by a solution injection method, or performing atomic layer deposition of Zn or Sn oxide on the surface of the first shell layer to form a second shell layer.
6. The method for preparing a composite cathode of a proton ceramic fuel cell according to claim 4, characterized in that: In S4, the solution injection method specifically comprises: preparing a precursor solution according to the stoichiometric ratio of lanthanum calcium iron tungsten perovskite type oxide, and then injecting the precursor solution into the surface of the first shell layer, and forming the second shell layer after calcination.
7. The method for preparing a composite cathode of a proton ceramic fuel cell according to claim 4, characterized in that: In S4, the surface deposition uses diethyl zinc or tin tetrachloride as a precursor, and deposits ZnO or SnO2 on the surface of the first shell layer by atomic layer deposition, or first deposits ZnO and then deposits SnO2 to form a SnO2@ZnO composite layer.
8. The method for preparing a composite cathode of a proton ceramic fuel cell according to claim 7, characterized in that: The deposition amount of the second shell layer is 50 to 150 cycles.
9. The method for preparing a composite cathode of a proton ceramic fuel cell according to claim 5, characterized in that: The electrolyte is a proton conductor having the same elemental composition as the proton conductor material forming the cathode skeleton.
10. A proton ceramic fuel cell, comprising the proton ceramic fuel cell composite cathode according to any one of claims 1 to 4.
